Proceedings of the 1st International Conference on Science and Technology in Administration and Management Information, ICSTIAM 2021
DOI: 10.4108/eai.17-7-2019.2302054
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of The Cybercrime Prevention Policy at The Metro Jaya Police Station in Central Jakarta

Abstract: The research aims to determine the implementation of policies regarding cybercrime applications at the Metro Jaya Police, Central Jakarta in accordance with the Electronic Transactions of Electronic Information and / or Electronic Documents regulations. The basic theory used in this research is Edward III (1980), which states that policy implementation is influenced by communication, resources, disposition, and bureaucratic structures. This study used a qualitative descriptive method by interviewing several in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Research finding on Azuari (2017:19) were that there is a significant correlation between students' personality type and their speaking achievement of the fifth semester undergraduate EFL student at English Education Study Program of UIN Raden Fatah Palembang. (Ulwiyah and Djuhan 2021 : 118) the results showed that (1) there were differences in the interaction between extroverted and introverted personalities when using the social studies learning and learning method (2) for students with introverted personalities to be more suitable to use the discussion method, while extroverted personalities were able to adapt (3) social interactions were created well thus in accordance with social psychology in which they are able to behave, think, in the context of social situations (Damayanti et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Research finding on Azuari (2017:19) were that there is a significant correlation between students' personality type and their speaking achievement of the fifth semester undergraduate EFL student at English Education Study Program of UIN Raden Fatah Palembang. (Ulwiyah and Djuhan 2021 : 118) the results showed that (1) there were differences in the interaction between extroverted and introverted personalities when using the social studies learning and learning method (2) for students with introverted personalities to be more suitable to use the discussion method, while extroverted personalities were able to adapt (3) social interactions were created well thus in accordance with social psychology in which they are able to behave, think, in the context of social situations (Damayanti et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…After reviewing the data analysis presented in the table, it can be concluded that the Video Tutorial has a greater impact on the writing procedure text of seventh grade students at SMP Negeri 1 Pematang Siantar (Damayanti & Ismowati, 2021). The researcher found some findings as follows:…”
Section: Research Findingmentioning
confidence: 94%
“…Silalahi, Blakers [13] investigated the role of solar photovoltaic (PV) in Indonesia and reported a vast potential for solar rooftop PV to meet future demand and that Indonesia has abundant space to deploy enough solar systems, including rooftop PV. Hapsari Damayanti, Tumiwa [14] investigated four different scenarios with various access factors. They determined the suitable roof space for PV in Indonesia to be between 20% to 42% of the total roof area, with the average being 33%.…”
Section: Introductionmentioning
confidence: 99%